Konsep Pengendalian Teknologi Informasi di Lembaga Keuangan Bank: Information Technology Control Concepts in Bank Financial Institutions - Nasution, Maimanah Salsabila; Fauzan Fahruza Situmorang (LPPM Institut Studi Islam Sunan Doe, 2022)
One method to improve banking service standards is to train staff to make better use of information technology. In terms of further lending of funds to consumers, financial institutions such as banks play a deterrent role. Accounting information systems are used similarly in Islamic banking as in traditional banking, both conceptually and fundamentally. This study aims to find out about the concept of information technology control in bank financial institutions. This study uses a qualitative method with a phenomenological approach. Data collection techniques were carried out through observation and interviews. The results of this study are that using new communication technologies more carefully can increase customer happiness in the face of increasing competition in the banking industry and government deregulation measures to prevent cybercrime. In addition to the impact of competition, IT systems are also affected by workplace capacity, regional influence, and improvements in information technology (especially computer and communication technology) (especially computer and communication technology). Decisions made during the development of an existing or new information system must consider the definition, construction, and implementation phases. Information systems must also be adaptable, user-friendly, real-time, database-driven and integrated.